Design and fabrication of a polymer based directional coupler thermooptic switch - Mohd. Supa'at, Abu Samah (2004)
This thesis is concerned with the development of optical switches, which are essential components for wavelength division multiplexed optical networks. A waveguide type 2X2 thermooptic polymer optical switch based on generalized directional coupler interferometer operating at 1550 nm for singlemode operation has been designed and fabricated. Three research topics in the development of optical switches were unified through the use of polymer materials in photonic devices. The topics are; a unique formulation of two and three dimensional model of planar dielectric waveguide using MATLAB for accurate simulation of straight waveguides and waveguides bend. Secondly, a thermal analysis used for the calculation of the temperature profile and the resulting phase shift due to thin film heater electrodes in polymers using MATLAB for switching functions and finally, the design, fabrication and measurement of 2X2 thermooptic polymer based optical switch. Optical propagation in dielectric waveguides has been analyzed using the semi analytical effective index method and numerical method based on finite difference approach. The iterative solution and successive over relaxation method have been sought for better results of the criterion of sufficient accuracy and improvement of speed of convergence respectively. A description of thermal analysis used for the calculation of the temperature profile and the resulting phase shift in polymer optical waveguide has been investigated. The resulting phase shift due to the induced temperature as a function of the thin film electrodes heater configuration and the applied power have been determined for future device implementation between two adjacent polymer waveguides. The device uses symmetrical and asymmetrical modes interference couplers to perform necessary passive power splitting operations. Electrically controlled gold heater electrodes and chromium heater pads for adhesion were used to perform the switching operation by altering the refractive index of the coupler arms. The new asymmetric structure in terms of index contrast difference between the cladding and waveguiding layers of 2X2 polymer switch was fabricated using ultraviolet curable acrylate adhesive polymers on silicon substrate using photolithography process. A switching time of 7 ms and a crosstalk value of -30 dB were measured. The insertion loss measured was 2 dB. It also has the advantage of being a low cost optical switch with a very low power consumption of 12.26 mW.